Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jsv.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of force distribution for a periodically supported beam subjected to moving loads

Abstract: In this study, a novel model for a periodically supported beam subjected to moving loads was developed using a periodicity condition on reaction forces. This condition, together with Fourier transforms and Dirac combs properties, forms a relation between the beam displacement and support reaction forces. This relation explains the force distribution to the supports, and holds for any type of support and foundation behaviors. Based on this relation, a system equivalence for a periodically supported beam is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
(6 reference statements)
2
19
0
1
Order By: Relevance
“…It is therefore very apt for parametric analyses aiming at fundamental understanding. Frequencydomain models have been applied in the past with different degrees of complexity and with different aims, ranging from very simple beam-on-elastic-foundation (BOEF) models [18][19][20][21][22] to more sophisticated twoor three-layer linear beam models accounting for discrete sleeper spacing and transient loading [23][24][25][26][27][28] and finally fully three-dimensional beam or plate on halfspace models (eventually with stratification), the latter ones with the aim of predicting environmental vibration due to moving trains [29][30][31][32][33][34]. Given the scope of the present study and its preliminary character, it is chosen to adopt a model that is on one hand no more complicated than strictly necessary, on the other hand able to describe all individual track components and take into account energy dissipation in the substructure or subsoil.…”
Section: Imentioning
confidence: 99%
“…It is therefore very apt for parametric analyses aiming at fundamental understanding. Frequencydomain models have been applied in the past with different degrees of complexity and with different aims, ranging from very simple beam-on-elastic-foundation (BOEF) models [18][19][20][21][22] to more sophisticated twoor three-layer linear beam models accounting for discrete sleeper spacing and transient loading [23][24][25][26][27][28] and finally fully three-dimensional beam or plate on halfspace models (eventually with stratification), the latter ones with the aim of predicting environmental vibration due to moving trains [29][30][31][32][33][34]. Given the scope of the present study and its preliminary character, it is chosen to adopt a model that is on one hand no more complicated than strictly necessary, on the other hand able to describe all individual track components and take into account energy dissipation in the substructure or subsoil.…”
Section: Imentioning
confidence: 99%
“…In the steady-state, we suppose that all sleepers have the same response but with a delay which is equal to the time for the moving forces to cover the distance between two sleepers. By using this condition, Hoang et al [1] have shown a relation between the beam displacement (w r ) and reaction force (R) at the sleeper position as follows : Figure 1: Periodically supported beam subjected to moving loads where K(!) and Q(!)…”
Section: Formulationsmentioning
confidence: 99%
“…In addition, the sleeper dynamic response is important because it affects the stability of the railway track and the maximum speed of the train. Substantial researches using analytic methods for rail track have been carried out, for example : the effect of wheel-rail contact forces [17,18] or the vibration of the railway track (by considering the model of a ballasted track with discrete supports [8,9,13,14,1] or the model of the infinite beam placed on a continuous foundation [10,7,6,11]). The studies of each component of the rail track were performed on the rail [19,16,15], or on the ballast [20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposal was developed in joint work [2][3][4][5][6][7]. It must be clarified that Bernstein's previously proposed "spectral function" method was used only to analyze systems with fixed parameters without considering friction [10,13]. At work [6] Zoryj L.M.…”
Section: Introductionmentioning
confidence: 99%